Process Oriented Guided Inquiry Learning in Australian secondary science classrooms - Dogra, Aneeta (Curtin University, 2021)
Process Oriented Guided Inquiry Learning (POGIL) is a student-centred active learning pedagogy, adapted for Australian secondary classes for the first time. This study utilised action research in a teacher-as-researcher model and applied quasi-experimental mixed methods to identify key positive cognitive and affective gains in the POGIL classroom. This research demonstrated the efficacy of meeting curricular goals, like scientific inquiry, on a number of dimensions using this pedagogy and supports further implementation of POGIL.